Connected health in US, EU, and China: opportunities to accelerate regulation of connected health technologies to optimize their role in medicines development - Awad, Susan; Aljuburi, Lina; Lumsden, Rebecca S.; Mpandzou, Marya; Marinus, Roelie (Frontiers in Medicine, 2023)
Connected health technology is playing an increasingly important role in healthcare. The power, complexity, functionality, and accessibility of connected health technologies are increasing rapidly, showing promise for improved and more equitable healthcare outcomes. They are integral to the lifecycle of medical products, from discovery and development to manufacturing and ultimately to the patient. The spectrum of integration between medical products and digital technologies ranges from non-drug specific solutions for supporting adherence or patient monitoring, which may or may not require regulatory approval, to digital therapeutics and software-containing combination products, which make claims supported by clinical evidence. The exponential increase and rapid evolution of connected health technologies – and the accompanying possibilities for innovative healthcare interventions, delivery systems, and clinical trial designs – pose new and complicated regulatory challenges. Currently, connected health may involve the use of regulated medical devices, including software as a medical device, or consumer products, such as wearables or apps, that fall under regulatory discretion. In this paper we examine how connected health technologies intersect with the development and lifecycle of medical products, how they are impacted by existing regulatory frameworks in the US, EU, and China, and propose future focus areas of activity.